Synthesis and characterization of carbomer-based hydrogels for drug delivery applications. Issue 11 (24th July 2021) - Rossetti, Arianna; Pizzetti, Fabio; Rossi, Filippo; Mauri, Emanuele; Borghi, Elisa; Ottaviano, Emerenziana; Sacchetti, Alessandro
Abstract: Drug delivery systems for the controlled and targeted release of drugs are in continuous development nowadays, allowing to benefit of ever better and more effective therapies. Chemical engineers thanks to their multidisciplinary preparation ranging from a thorough knowledge of transport phenomena to the transformations of matter, play a fundamental role in the development of these innovative systems. In this work, we developed and characterized some innovative polymer-based hydrogels, to study their efficacy as systems for controlled release of drugs and to verify the possibility of inherent antimicrobial properties for these hydrogels. We report here the use of two different Carbomer-based formulations, particularly promising for their simplicity and potential applications. In the first case, polyethylene glycol was used as the cross-linking agent and the material was obtained through a physical-chemical transition by microwave irradiation. In the other case, a polyetherdiamine was employed and the reticulation was achieved by chemical transformation with the use of a specific coupling agent. The materials were characterized in their structure, swelling behavior, rheological properties, morphology and antimicrobial activity. Finally, the effectiveness of these formulations as systems for the controlled release of drugs was tested using mimetic drugs of various sizes. Graphical Abstract: UF0001